Reorienting the Economic Rights of Creators: A Constitutional Analysis of Copyright Licensing Post-Constitutional Court Decision No. 28/PUU-XXIII/2025 - Rifqi Pratama Putra; Dwi Suryahartati; Zeni Sunarti (Civiliza Publishing, 2025)
This research examines the implications of Constitutional Court Decision No. 28/PUU-XXIII/2025 on digital copyright licensing in Indonesia. The study addresses the anomaly where rapid creative industry growth fails to enhance creator welfare due to exploitative